The effect of Tabata exercises on muscle power and running speed in under-20 200 metres runners - Ali, Muntadher M.; Hussain, Ali Ab.; Jasim, Mokhalad M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The primary aim of the present study was to formulate a set of Tabata-style exercises and to identify the effect of these exercises for performance stages on power characteristic of speed and achievement of 200m for runners under 20 years old. The present study had an experimental pre-test & post-test design to solve the research problem of the study. 200-meter race runners were identified as the research community in Najaf Governorate for the 2020-2021 sports season. A total of 6 runners were selected as the participants for the study. The present study was conducted on 200m runners in the Najaf International Stadium, in Najaf governorate within the timeframe of June 2021 to September 2021. Based on the findings of the present study, the researchers concluded that the application of exercises in Tabata style aided in developing the power characteristic of speed for the two legs of the participants of the experimental group.